PENGARUH ORGANIZATIONAL CULTURE TERHADAP EMPLOYEE PERFORMANCE - Umi Wahyuni; Gazali Gazali (Al-Amien Prenduan for Islamic Institute, 2021)
This study aims to determine and analyze the performance of employees at the UPT Puskesmas Waru. In this regard, how employees can work well with the influence of culture is an interesting discussion to discuss. The sample used is a saturated sample that uses all members of the population as a sample who visited 70 people. The data collection method used is a questionnaire. The data were analyzed by simple regression with the help of SPSS 16.0 software for windows. The results showed that organizational culture had a significant effect on employee performance at UPT Puskesmas Waru.